Preparation method of amoxicillin crystals
By acidizing treatment and controlling the pH value in amoxicillin enzymatic condensation solution, the problem of insufficient particle size of amoxicillin is solved, and the preparation of large particle size is achieved, and the stability of drug preparations and capsules are improved. Production efficiency of the preparation.
Patent Information
- Application Number
- CN202211037561.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-08-26
AI Technical Summary
The particle size of the existing amoxicillin crystals is not large enough, which affects the quality and stability of drug preparations, especially in the production process of capsule preparations, resulting in problems such as dust flying and inconsistent preparation dosage.
By acidizing the enzyme condensation solution, the pH value is reduced to <0.2, and ammonia water is added dropwise under stirring, the pH value is controlled to be between 2 and 5, and the crystals are cultivated for 20 to 40 minutes, and then the temperature is reduced to 0°C to 10° C., filtered, washed and dried to obtain amoxicillin crystals with suitable large particle size.
The particle size of amoxicillin crystals has been improved, with Dv(10) ranging from 10 to 15 μm, Dv(50) ranging from 45 to 60 μm, and Dv(90) ranging from 145 to 165 μm, which has enhanced the stability of drug preparations and the production efficiency of capsule preparations. , improves the purity and yield of the product.
Smart Images

Figure BDA0003817781670000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of pharmaceutical compound crystals, and more specifically, relates to a method for preparing amoxicillin crystals with effectively increased particle size and high purity. The amoxicillin crystals have a suitable large particle size, wherein Dv(10) is 10-15 μm, Dv(50) is 45-60 μm, and Dv(90) is 145-165 μm. Amoxicillin with a suitable large particle size can be effectively used to prepare amoxicillin pharmaceutical preparations, especially capsule preparations. Background Art
[0002] Amoxicillin, also known as amoxicillin or amoxil, is one of the most commonly used broad-spectrum β-lactam antibiotics of the penicillin class. Amoxicillin has a strong bactericidal effect, is broad-spectrum, highly effective, and has few toxic and side effects. It has been widely used in the field of medicine and health. Its preparations mainly include capsules, tablets, granules, dispersible tablets, etc.
[0003] There are two main methods for synthesizing amoxicillin: one is chemical synthesis, and the other is enzyme-catalyzed synthesis (enzyme method for short). The use of enzyme method to synthesize amoxicillin can avoid the use of organic solvents, and the reaction conditions are mild, energy consumption is low, operation is easy, and the whole process is green and environmentally friendly. At the same time, the purity of amoxicillin synthesized by enzyme method is higher than that of chemically synthesized products, and the safety and stability of the drug are greatly improved. Therefore, the enzyme method has gradually replaced the chemical synthesis method and become the main method for the production of amoxicillin.
[0004] In the process of enzymatic synthesis of amoxicillin, D-p-hydroxyphenylglycine methyl ester is mostly used as the acyl side chain donor, which is condensed with 6-APA (6-aminopenicillanic acid) under the catalysis of immobilized penicillin acylase for synthesis to generate amoxicillin, and then amoxicillin crystals are obtained by crystallization. In the traditional crystallization process, acid / alkali solution is added to the amoxicillin condensation solution to adjust its pH value to the isoelectric point of amoxicillin 4-5. Under the isoelectric point conditions, the charge carried by amoxicillin is zero, and crystals begin to form at this time. The formation and growth of crystal nuclei are controlled by controlling the pH, temperature and stirring during the crystallization process.
[0005] Amoxicillin with a suitable large particle size has a positive impact on the filtration, washing, drying, packaging and preparation of amoxicillin pharmaceutical preparations (especially the canning of capsule preparations) after crystallization, avoiding dust in the operating environment and ensuring the consistency of the amount of amoxicillin per unit preparation.
[0006] Qiao Wenqing, Bai Jun, et al. reported a crystallization process of amoxicillin with large crystals and good stability in "Research on Changing Crystallization Process to Improve the Quality of Amoxicillin" ("Hebei Chemical Industry", Vol. 33, No. 8, August 2010, pp. 27-31), in which an aqueous solution of amoxicillin hydrochloride with a pH of 1.0 and ammonia water (concentration 10%-12%) were slowly added to a reactor at the same time, the pH value was controlled to be maintained at 5.0-5.10, the temperature was controlled at 1°C-5°C for crystal cultivation, and then filtered, washed, and dried to obtain amoxicillin dry powder. However, the specific particle size and yield were not mentioned in the article.
[0007] Wang Yanyan, Zhu Ke and others reported the effects of stirring speed, stirring intensity, crystal seed, cooling temperature and other factors on crystallization in "Research on the Crystallization Process of Amoxicillin" ("Hebei Chemical Industry", Vol. 30, No. 1, January 2007, pp. 27-31). Wang Yanyan, Zhu Ke and others' research on the crystallization process of amoxicillin still focuses on the control of process conditions such as stirring speed, stirring intensity, crystal seed, cooling temperature, etc., which belongs to the fine-tuning of the crystallization process.
[0008] Amoxicillin is a broad-spectrum penicillin antibiotic with a wide range of applications and many manufacturers. Only products with good quality and high yield can be competitive in the fierce market. Therefore, manufacturers are continuously researching and improving the process of amoxicillin crystallization. Summary of the invention
[0009] Based on the above problems, the object of the present invention is to provide a method for preparing amoxicillin crystals with effectively increased particle size and high purity, wherein the amoxicillin crystals have a suitably large particle size, wherein Dv(10) is 10-15 μm, Dv(50) is 45-60 μm, and Dv(90) is 145-165 μm. Amoxicillin with a suitably large particle size can be effectively used to prepare amoxicillin pharmaceutical preparations, especially capsule preparations, and the yield of the preparation method is improved.
[0010] According to the present invention, the preparation method of amoxicillin crystals provided by the present invention comprises: acidifying an amoxicillin enzymatic condensation liquid with hydrochloric acid at 20°C to 30°C, so that the pH of the condensation liquid is less than 0.2, and the molar ratio of amoxicillin to HCl is 1:5.8-7.6; then dripping ammonia water into the acidified condensation liquid under stirring until the pH is 2-3, and when turbidity begins to appear, stopping dripping ammonia water, and growing crystals for 20-40 minutes; continuing to drip ammonia water until the pH value is 4-5, cooling to 0°C to 10°C, stirring and growing crystals, filtering, washing, and drying to obtain amoxicillin crystal powder.
[0011] The following is a more detailed description of the method for preparing the amoxicillin crystals of the present invention.
[0012] In the present invention, the amoxicillin enzymatic condensation liquid is a suspension obtained by condensing 6-APA (6-aminopenicillanic acid) and D-p-hydroxyphenylglycine methyl ester under the catalysis of immobilized penicillin acylase for synthesis, and filtering out the immobilized penicillin acylase for synthesis to obtain the condensation reaction liquid, which usually contains 100 to 110 mg / ml of amoxicillin and has a pH of 6 to 7, preferably 6.5 to 6.9.
[0013] The amoxicillin enzymatic condensation liquid is acidified with hydrochloric acid to completely dissolve the amoxicillin. The hydrochloric acid used is generally commercially available concentrated hydrochloric acid, for example, hydrochloric acid with a mass fraction of 32% to 35%. During the acidification treatment, the stirring speed can be generally controlled at 250 to 400 r / min, preferably 250 to 300 r / min, and hydrochloric acid is added under stirring so that the pH of the condensation liquid is less than 0.2, preferably 0.1 to 0.19, and the molar ratio of amoxicillin to HCl is 1:5.8 to 7.6, preferably 1:6.2 to 6.9. The amoxicillin enzymatic condensation liquid is a clear solution after acidification. In order to ensure that the solution is clear and clear to obtain pure amoxicillin crystals during crystallization, it is preferred to filter the acidified condensation liquid with an organic microporous filter membrane (e.g., a 0.45 μm microporous filter membrane), and the amoxicillin content in the filtered condensation liquid is 85 to 95 mg / ml.
[0014] During the acidification treatment, since amoxicillin hydrochloride is easy to precipitate, the temperature is controlled at 20°C to 30°C; at 20°C to 30°C, hydrochloric acid is added to acidify to pH < 0.2, the amount of HCl is 5.8-7.6 times (molar multiples) of the amount of amoxicillin substance, and the acidified liquid is filtered with a 0.45μm organic microporous filter membrane. This acidification process is to ensure that amoxicillin is completely and thoroughly dissolved and turned into a single molecule state, and to avoid incomplete dissolution of amoxicillin, inducing collision between amoxicillin molecules and precipitation of amoxicillin hydrochloride.
[0015] Then, ammonia water is added dropwise to the acidified filtered condensation liquid under stirring at 20°C to 30°C. The ammonia water used is generally commercially available concentrated ammonia water, for example, ammonia water with a mass fraction of 23% to 26%. In addition, the stirring speed is generally controlled at 20 to 50 r / min. In this process, ammonia water is added dropwise to the acidified condensation liquid until the pH value is 2-3. When turbidity begins to appear, the addition of ammonia water is stopped, and the crystal is stirred for 20-40 minutes. This process converts amoxicillin hydrochloride into amoxicillin molecules and ammonium chloride inorganic salts. The process is carried out slowly depending on the time of ammonia water addition, thereby regulating the probability of collision between amoxicillin molecules and gradually increasing the size of the crystals. Then, ammonia water is continued to be added dropwise until the pH value is 4-5, and pH=5 is the best. A large or small pH value will cause the amoxicillin crystals to dissolve, thereby reducing the product yield. Therefore, the most important thing in this process is to stabilize the pH value, cool to 0°C-10°C, preferably 4°C-5°C, stir and grow the crystals at 20-50r / min, and then filter, wash and dry to obtain amoxicillin crystal powder.
[0016] Beneficial Effects
[0017] The preparation method of amoxicillin crystals of the present invention has the following main improvements and features:
[0018] During the acidification process, by adding high molar number of hydrochloric acid to the amoxicillin enzymatic condensation liquid, firstly, amoxicillin can be dissolved more quickly and thoroughly, and the undissolved amoxicillin wrapped with impurities can be prevented from acting as crystal nuclei to adsorb dissolved amoxicillin, resulting in an increase in impurities in amoxicillin crystals; secondly, the amoxicillin concentration can be reduced, the collision probability and frequency of amoxicillin can be reduced, the crystallization can be relatively slow, and the crystallization can be avoided, which is conducive to further increasing the crystal particle size; thirdly, after the acidification liquid is added with ammonia water, more ammonium chloride inorganic salts will be formed. On the one hand, the inorganic salts can reduce the solubility of amoxicillin and improve the yield; on the other hand, more crystal skeletons can be provided for amoxicillin ions, which is conducive to the attachment of amoxicillin ions, making the crystals easier to collide and grow, thereby increasing the crystal particle size.
[0019] According to the present invention, the obtained amoxicillin crystals have a suitably large particle size, wherein Dv(10) is 10-15 μm, Dv(50) is 45-60 μm, and Dv(90) is 145-165 μm. Amoxicillin with a suitably large particle size can be effectively used to prepare amoxicillin pharmaceutical preparations, especially capsule preparations. In addition, the obtained amoxicillin crystals have a high yield of 92%-95% and high purity. DETAILED DESCRIPTION
[0020] The preparation method of amoxicillin crystals of the present invention is further described in detail below through examples, and the protection scope of the present invention is not limited to the following examples, which are listed only for illustrative purposes and are not intended to limit the present invention in any way.
[0021] Example 1
[0022] Take 190mL of amoxicillin enzymatic condensation liquid (among which, the amoxicillin content is 104.35mg / ml, pH 6.79) and place it in a 500mL four-necked flask, adjust its temperature to 28.0°C with a water bath, start stirring at 300r / min, and add 34.0mL of hydrochloric acid (commercially available, mass fraction 33.2%) within 2 minutes. At this time, the condensation liquid has been completely dissolved and clear. The amoxicillin content in the acidified liquid is 88.21mg / mL, the pH is 0.15, the temperature is 28.5°C, and the amoxicillin:HCl molar ratio is 1:6.70.
[0023] The acidified solution was filtered with a 0.45 μm microporous filter membrane and placed in a 500 mL four-necked flask. The temperature was adjusted to 28.0°C with a water bath and stirring was started at 30 r / min. After the temperature and rotation speed were stable, ammonia water (commercially available, 25% by mass) was added dropwise. When 27 mL of ammonia water was added, the pH was 2.41 and the temperature was 28.5°C. At this time, the solution became turbid from clear and transparent. At the same time, the addition of ammonia water was stopped and initial stirring was performed for crystal growth. After 32 minutes, the pH stabilized at 1.85 and the particles in the crystallization liquid were sandy. If stirring was stopped at this time, the crystals would quickly settle to the bottom of the bottle. The above stirring speed was maintained and 4.5 mL of ammonia water was added dropwise. At this time, the pH was 4.98 and the temperature was 28.0°C. Subsequently, secondary crystal growth was started, and the crystallization liquid was slowly cooled to 4-5°C and stirred at the same speed for 2 hours.
[0024] Then, the above crystal solution was filtered with ordinary filter paper. The amoxicillin crystals were granular and easy to filter. After washing with water, they were dried to obtain 21.23 g of amoxicillin trihydrate dry powder.
[0025] The particle size of the dry powder obtained above was measured using a Malvern laser particle size analyzer (equipment model Mastersizer 3000), and the results are shown in Table 1 below.
[0026] Agilent high performance liquid chromatograph (equipment model 1260) was used to analyze the content and related impurities. The results are shown in Table 2 below.
[0027] Example 2
[0028] Take 190mL of amoxicillin enzymatic condensation liquid (among which, the amoxicillin content is 106.78mg / ml, pH 6.88) and place it in a 500mL four-necked flask, adjust its temperature to 28.0°C with a water bath, start stirring at 300r / min, and add 34.2mL of hydrochloric acid (commercially available, mass fraction 33.2%) within 2 minutes. At this time, the condensation liquid has been completely dissolved and clear. The amoxicillin content in the acidified liquid is 90.18mg / mL, the pH is 0.17, the temperature is 28.5°C, and the amoxicillin:HCl molar ratio is 1:6.61.
[0029] The above acidified solution was filtered with a 0.45 μm microporous filter membrane, placed in a 500 mL four-necked flask, and the temperature was adjusted to 28.0°C with a water bath. Stirring was started at 30 r / min. After the temperature and rotation speed were stable, ammonia water (commercially available, mass fraction 25%) was added dropwise. When 27.5 mL of ammonia water was added, the pH was 2.55 and the temperature was 29.0°C. At this time, the clear and transparent solution began to become turbid. At the same time, the ammonia water addition was stopped, and preliminary stirring and crystal cultivation were carried out. After 29 minutes, the pH stabilized at 1.88, and the particles in the crystallization liquid were sandy. If stirring was stopped at this time, the crystals would quickly settle to the bottom of the bottle. Maintaining the above stirring speed, 4.6 mL of ammonia water was continued to be added dropwise. At this time, the pH was 5.04 and the temperature was 28.0°C. Subsequently, secondary crystal cultivation was started, and the crystallization liquid was slowly cooled to 4-5°C, and the crystal was stirred at the same speed for 2 hours.
[0030] Then, the above crystal liquid was filtered with ordinary filter paper. The amoxicillin crystals were granular and easy to filter. After washing with water, they were dried to obtain 21.45 g of amoxicillin trihydrate dry powder.
[0031] The particle size of the dry powder obtained above was measured using a Malvern laser particle size analyzer (equipment model Mastersizer 3000), and the results are shown in Table 1 below.
[0032] The content and related impurities were analyzed using Agilent high performance liquid chromatograph (equipment model 1260), and the results are shown in Table 2 below.
[0033] Example 3
[0034] Take 190mL of amoxicillin enzymatic condensation liquid (among which, the amoxicillin content is 107.28mg / ml, pH 6.77) and place it in a 500mL four-necked flask, adjust its temperature to 28.0°C with a water bath, start stirring at 300r / min, and add 34.1mL of hydrochloric acid (commercially available, mass fraction 33.2%) within 2 minutes. At this time, the condensation liquid has been completely dissolved and clear. The amoxicillin content in the acidified liquid is 90.32mg / mL, the pH is 0.17, the temperature is 28.5°C, and the amoxicillin:HCl molar ratio is 1:6.59.
[0035] The acidified solution was filtered with a 0.45 μm microporous filter membrane and placed in a 500 mL four-necked flask. The temperature was adjusted to 28.0°C with a water bath and stirring was started at 30 r / min. After the temperature and rotation speed were stable, ammonia water (commercially available, 25% by mass) was added dropwise. When 27.0 mL of ammonia water was added, the pH was 2.35 and the temperature was 29.0°C. At this time, the solution became turbid from clear and transparent. At the same time, the addition of ammonia water was stopped and initial stirring was performed for crystal growth. After 35 minutes, the pH stabilized at 1.91 and the particles in the crystallization liquid were sandy. If stirring was stopped at this time, the crystals would quickly settle to the bottom of the bottle. The above stirring speed was maintained and 4.5 mL of ammonia water was added dropwise. At this time, the pH was 5.02 and the temperature was 28.0°C. Subsequently, secondary crystal growth was started, the crystallization liquid was slowly cooled to 4-5°C, and the crystal was grown for 2 hours with stirring at the same speed.
[0036] Then, the above crystal liquid was filtered with ordinary filter paper. The amoxicillin crystals were granular and easy to filter. After washing with water, they were dried to obtain 21.78 g of amoxicillin trihydrate dry powder.
[0037] The particle size of the dry powder obtained above was measured using a Malvern laser particle size analyzer (equipment model Mastersizer 3000), and the results are shown in Table 1 below.
[0038] Agilent high performance liquid chromatograph (equipment model 1260) was used to analyze the content and related impurities. The results are shown in Table 2 below.
[0039] Comparative Example 1 (Traditional Crystallization Process)
[0040] Take 190mL of amoxicillin enzymatic condensation liquid (among which, the amoxicillin content is 106.42mg / ml, pH 6.79) and place it in a 500mL four-necked flask, adjust its temperature to 28.0°C with a water bath, start stirring at 300r / min, and add 9.0mL of hydrochloric acid (commercially available, mass fraction 33.2%) within 2 minutes. At this time, the condensation liquid has a clear appearance. The amoxicillin content in the acidified liquid is 101.58mg / mL, the pH is 0.93, the temperature is 28.5°C, and the amoxicillin:HCl molar ratio is 1:1.73.
[0041] The acidified liquid was filtered with a 0.45 μm microporous filter membrane, placed in a 500 mL four-necked flask, and the temperature was adjusted to 28.0°C with a water bath. Stirring was started at 30 r / min. After the temperature and rotation speed were stable, ammonia water (commercially available, 25% by mass) was added dropwise. When 4 mL of ammonia water was added, the pH was 1.45 and the temperature was 28.0°C. At this time, the clear liquid began to become turbid. At the same time, the addition of ammonia water was stopped, and preliminary stirring for crystal growth was carried out. After 30 minutes, the pH was stabilized at 1.35, and the crystal liquid was in a paste state. Stirring was maintained at the same speed and 4.3 mL of ammonia water was continued to be added dropwise. At this time, the pH was 4.98 and the temperature was 28.0°C. Secondary crystal growth was started, the crystal liquid was cooled to 4-5°C, and the crystal was grown for 2 hours with stirring at the same speed.
[0042] Then, the above crystal liquid was filtered with ordinary filter paper. The amoxicillin crystals were in the form of a surface and difficult to filter. After washing with water, they were dried to obtain 20.34 g of amoxicillin trihydrate dry powder.
[0043] The particle size of the dry powder obtained above was measured using a Malvern laser particle size analyzer (equipment model Mastersizer 3000), and the results are shown in Table 1 below.
[0044] Agilent high performance liquid chromatograph (equipment model 1260) was used to analyze the content and related impurities. The results are shown in Table 2 below.
[0045] Comparative Example 2 (Traditional Crystallization Process)
[0046] Take 190mL of amoxicillin enzymatic condensation liquid (among which, the amoxicillin content is 108.57mg / ml, pH 6.81) and place it in a 500mL four-necked flask, adjust its temperature to 28.0°C with a water bath, start stirring at 300r / min, and add 8.8mL of hydrochloric acid (commercially available, mass fraction 33.2%) within 2 minutes. At this time, the condensation liquid has a clear appearance. The amoxicillin content in the acidified liquid is 103.64mg / mL, the pH is 0.98, the temperature is 28.5°C, and the amoxicillin:HCl molar ratio is 1:1.66.
[0047] The acidified solution was filtered through a 0.45 μm microporous filter membrane, placed in a 500 mL four-necked flask, and the temperature was adjusted to 28.0°C with a water bath. Stirring was started at 30 r / min. After the temperature and rotation speed were stable, ammonia water (commercially available, 25% by mass) was added dropwise. When 3.9 mL of ammonia water was added, the pH was 1.51 and the temperature was 28.0°C. At this time, the solution became turbid from clear and transparent. At the same time, the addition of ammonia water was stopped, and preliminary stirring was performed for crystal growth. After 35 minutes, the pH stabilized at 1.42, and the crystallization liquid was in a paste state. Stirring was maintained at the same speed, and 4.2 mL of ammonia water was continued to be added dropwise. At this time, the pH was 4.91 and the temperature was 28.0°C. Secondary crystal growth was started, the crystallization liquid was cooled to 4-5°C, and the crystal was grown for 2 hours with stirring at the same speed.
[0048] Then, the above crystal solution was filtered with ordinary filter paper. The amoxicillin crystals were in the form of a surface and difficult to filter. After washing with water, they were dried to obtain 20.79 g of amoxicillin trihydrate dry powder.
[0049] The particle size of the dry powder obtained above was measured using a Malvern laser particle size analyzer (equipment model Mastersizer 3000), and the results are shown in Table 1 below.
[0050] Agilent high performance liquid chromatograph (equipment model 1260) was used to analyze the content and related impurities. The results are shown in Table 2 below.
[0051] Comparative Example 3 (Traditional Crystallization Process)
[0052] Take 190mL of amoxicillin enzymatic condensation liquid (among which, the amoxicillin content is 106.88mg / ml, pH 6.74) and place it in a 500mL four-necked flask, adjust its temperature to 28.0°C with a water bath, start stirring at 300r / min, and add 8.9mL of hydrochloric acid (commercially available, mass fraction 33.2%) within 2 minutes. At this time, the condensation liquid has a clear appearance. The amoxicillin content in the acidified liquid is 101.54mg / mL, the pH is 0.81, the temperature is 28.5°C, and the amoxicillin:HCl molar ratio is 1:1.71.
[0053] The acidified solution was filtered through a 0.45 μm microporous filter membrane and placed in a 500 mL four-necked flask. The temperature was adjusted to 28.0°C with a water bath and stirring was started at 30 r / min. After the temperature and rotation speed were stable, ammonia water (commercially available, 25% by mass) was added dropwise. When 4.2 mL of ammonia water was added, the pH was 1.67 and the temperature was 28.0°C. At this time, the solution became turbid from clear and transparent. At the same time, the addition of ammonia water was stopped and preliminary stirring was performed for crystal growth. After 33 minutes, the pH stabilized at 1.31 and the crystallization liquid was in a paste state. Stirring was maintained at the same speed and 4.0 mL of ammonia water was added dropwise. At this time, the pH was 4.92 and the temperature was 28.0°C. Secondary crystal growth was started, the crystallization liquid was cooled to 4-5°C, and the crystal was grown for 2 hours with stirring at the same speed.
[0054] Then, the above crystal solution was filtered with ordinary filter paper. The amoxicillin crystals were in a planar shape and difficult to filter. After washing with water, they were dried to obtain 20.01 g of amoxicillin trihydrate dry powder.
[0055] The particle size of the dry powder obtained above was measured using a Malvern laser particle size analyzer (equipment model Mastersizer 3000), and the results are shown in Table 1 below.
[0056] Agilent high performance liquid chromatograph (equipment model 1260) was used, and the content and related impurities are shown in Table 2 below.
[0057] Table 1 Amoxicillin crystal particle size prepared in Examples 1-3 and Comparative Examples 1-3
[0058]
[0059] Table 2 Yield and purity of amoxicillin crystals prepared in Examples 1-3 and Comparative Examples 1-3
[0060] project Yield % Moisture% Dry content% Single impurity % Total impurities% Example 1 93.75 12.5 99.85 0.06 0.11 Example 2 92.92 12.6 99.91 0.07 0.10 Example 3 93.75 12.6 99.78 0.06 0.11 Comparative Example 1 87.50 12.8 99.65 0.06 0.11 Comparative Example 2 87.92 12.7 99.71 0.08 0.13 Comparative Example 3 86.67 12.5 99.82 0.07 0.12
[0061] It can be seen that according to Examples 1-3 of the method for preparing amoxicillin crystals of the present invention, the prepared amoxicillin crystals have a suitably large particle size, Dv(10) is 10-15 μm, Dv(50) is 45-60 μm, and Dv(90) is 145-165 μm. Amoxicillin with a suitably large particle size can be effectively used to prepare amoxicillin pharmaceutical preparations, especially capsule preparations, and the yield of the preparation method is improved, and the product quality is good.
Claims
1. A method for preparing amoxicillin crystals, comprising: At 20°C to 30°C, hydrochloric acid is used to acidify the amoxicillin enzymatic condensation liquid so that the pH of the condensation liquid is 0.1 to 0.19, and the molar ratio of amoxicillin to HCl is 1:5.8 to 7.6; after the amoxicillin enzymatic condensation liquid is acidified, the acidified condensation liquid is filtered using an organic microporous filter membrane; then, ammonia water is dripped into the acidified condensation liquid under stirring until the pH value is 2 to 3, and when turbidity begins to appear, the dripping of ammonia water is stopped, and crystals are grown for 20 to 40 minutes; ammonia water is continued to be dripped until the pH value is 4 to 5, and the temperature is lowered to 0°C to 10°C, and the crystals are grown by stirring, and after filtering, washing and drying, amoxicillin crystal powder is obtained, wherein the amoxicillin crystals have a suitable large particle size, wherein Dv(10) is 10 to 15 μm, Dv(50) is 45 to 60 μm, and Dv(90) is 145 to 165 μm.
2. The method for preparing amoxicillin crystals according to claim 1, characterized in that: The amoxicillin enzymatic condensation liquid is prepared by condensing 6-aminopenicillanic acid and D-p-hydroxyphenylglycine methyl ester under the catalysis of immobilized penicillin acylase for synthesis, and filtering out the immobilized penicillin acylase for synthesis to obtain the condensation reaction liquid.
3. The method for preparing amoxicillin crystals according to claim 2, characterized in that: The amoxicillin enzymatic condensation liquid has an amoxicillin content of 100-110 mg / ml and a pH of 6-7.
4. The method for preparing amoxicillin crystals according to claim 1, wherein During the acidification treatment, hydrochloric acid is added while the stirring speed is controlled at 250-400 r / min, so that the pH of the condensation solution is 0.1-0.19, and the molar ratio of amoxicillin to HCl is 1:6.2-6.
9.
5. The method for preparing amoxicillin crystals according to claim 1, characterized in that: In the acidification treatment, the hydrochloric acid has a mass fraction of 32% to 35%.
6. The method for preparing amoxicillin crystals according to claim 1 or 4, characterized in that: Ammonia water is added dropwise to the acidified condensation liquid under stirring, and the stirring speed is controlled at 20-50 r / min.
7. The method for preparing amoxicillin crystals according to claim 1, characterized in that: The ammonia water has a mass fraction of 23% to 26%.
8. The method for preparing amoxicillin crystals according to claim 1, characterized in that: The temperature was lowered to 4-5°C, and the crystals were grown with stirring at 20-50 r / min. After filtering, washing and drying, amoxicillin crystal powder was obtained.
Citation Information
Patent Citations
Method for recycling amoxicillin mother solution
CN105567777A
Highly-water-soluble amoxicillin and preparation method thereof
CN109867687A
Continuous crystallization process of amoxicillin
CN111518119A
Process for preparing crystalline salts of amoxycillin
US20020137926A1
